A Novel Index for Prompt Prediction of Severity in Patients with Unstable Angina Pectoris. (3rd January 2020) - Bolatkale, Mustafa; Acara, Ahmet Cagdas
Abstract : Objectives . Rapid risk stratification by emergency department (ED) physicians to evaluate patients with chest pain for predicting the short-term occurrence of major adverse cardiac event (MACE) is crucial. The aim of this study was to investigate the predictive value of platelet-lymphocyte ratio (PLR) levels and compare with the modified heart score (m-HS) and stress testing to predict the severity of high-risk patients with unstable angina pectoris (UAP) in the ED. Methods . This study is prospective which included 316 patients with UAP and 316 control healthy subjects. The study took place from 01 April 2016, until 01 April 2017, in Medipol University. Result . The mean PLR levels in the UAP group were higher than those in the control group (p < 0.001 ). The mean PLR of the m-HS ≥4 group was higher than that in the m-HS ≤3 group (p < 0.001 ). The mean levels of PLR in the subgroups based on the stress testing positivity were higher than those in the stress testing negative subgroup (p < 0.001 ). PLR levels were positively correlated with the m-HS, stress testing, and treatment decision in this study ( r  = 0.559; p < 0.001 ; r  = 0.582; p < 0.001 ; r  = 0.789; p < 0.001, respectively). Conclusion . A positive correlation was determined with an increase in m-HS, treatment decision, and positive exercise testing as the PLR levels increased, indicating the severity of high risk of UAP in the ED.